Conquering new grounds: plant organellar C‐to‐U RNA editing factors can be functional in the plant cytosol - Thielen, Mirjam; Gärtner, Béla; Knoop, Volker; Schallenberg‐Rüdinger, Mareike; Lesch, Elena (The Plant journal : for cell and molecular biology, 2024)
SUMMARY Plant mitochondrial and chloroplast transcripts are subject to numerous events of specific cytidine‐to‐uridine (C‐to‐U) RNA editing to correct genetic information. Key protein factors for this process are specific RNA‐binding pentatricopeptide repeat (PPR) proteins, which are encoded in the nucleus and post‐translationally imported into the two endosymbiotic organelles. Despite hundreds of C‐to‐U editing sites in the plant organelles, no comparable editing has been found for nucleo‐cytosolic mRNAs raising the question why plant RNA editing is restricted to chloroplasts and mitochondria. Here, we addressed this issue in the model moss Physcomitrium patens, where all PPR‐type RNA editing factors comprise specific RNA‐binding and cytidine deamination functionalities in single proteins. To explore whether organelle‐type RNA editing can principally also take place in the plant cytosol, we expressed PPR56, PPR65 and PPR78, three editing factors recently shown to also function in a bacterial setup, together with cytosolic co‐transcribed native targets in Physcomitrium. While we obtained unsatisfying results upon their constitutive expression, we found strong cytosolic RNA editing under hormone‐inducible expression. Moreover, RNA‐Seq analyses revealed varying numbers of up to more than 900 off‐targets in other cytosolic transcripts. We conclude that PPR‐mediated C‐to‐U RNA editing is not per se incompatible with the plant cytosol but that its limited target specificity has restricted its occurrence to the much less complex transcriptomes of mitochondria and chloroplast in the course of evolution. Significance Statement We show that PPR‐type organelle RNA editing factors can principally also function in the plant cytosol but that their lack of targeting specificity likely restricts their occurrence in nature to chloroplasts and mitochondria. Our new approach of induced cytosolic expression will allow to much better characterize the RNA‐targeting properties of natural or artificially engineered PPR proteins in vivo in the future.